Peran Dinas Kehutanan Provinsi Kalimantan Tengah dalam Pengembangan Wisata Berkelanjutan di Kawasan Nyaru Menteng Arboretum Kota Palangka Raya - Apriyadi Apriyadi; Andi Saputra; Simson Oktelhanan Lukius (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the role of the Central Kalimantan Provincial Forestry Service in managing and developing sustainable tourism in the Nyaru Menteng Arboretum Urban Forest area in Palangka Raya City using George C. Edward III's public policy implementation framework. The Nyaru Menteng area, which previously functioned as an orangutan rehabilitation and reintroduction center, now faces transformation challenges from a conservation area to a sustainable tourism destination after its status change to non-forest state land. This research employs a qualitative method with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results indicate that the implementation of sustainable tourism development policies can be analyzed through Edward III's four variables: (1) communication—evidenced through the socialization of Central Kalimantan Governor Regulation Number 37 of 2021 and coordination with stakeholders; (2) resources—including budget allocation for tourism infrastructure development and deployment of 14 cleaning officers; (3) disposition—reflected in the commitment of apparatus in maintaining environmental sustainability and conservation education; and (4) bureaucratic structure—reflected in inter-unit coordination and implementation of SOPs for area management. These findings fill the research gap in literature regarding sustainable tourism policy implementation in urban forest areas post-wildlife rehabilitation in Indonesia.